TESTING AS A LANGUAGE ASSESSMENT TOOL: UKRAINIAN EXPERIENCE - Vysotska, Oksana (The Modern Higher Education Review, 2023)
There are lots of books devoted to test design techniques for teachers to critically evaluate and reflect on assessment items developed by them and for them. However, the problem is whether teachers, who are “jacks of all trades,” are assessment and test-writing literate, whether they are aware of assessment purposes, they understand and can interpret methods and principles of test item design. The question arises whether, with the help of tests, teachers can ensure valid inferences about test takers’ knowledge and skills, and whether teachers who become item writers and test designers have enough knowledge and skills for this complicated task. The article contributes to helping Ukrainian university teachers reflect on their assessment and evaluation knowledge and skills. Hopefully, the article may raise awareness of the importance of a deeper theoretical and practical expertise in high-quality assessment for language education. Besides, the article may stimulate teachers’ attention and focus on complicated problems around test creation, administration, and analysis.